Powtoon: A Digital Medium to Optimize Students’ Cultural Presentation in ELT Classroom - Lulud Oktaviani; Berlinda Mandasari (TEKNOSASTIK, 2020)
Facing industrial revolution 4.0 requires university students to provide themselves with a skill that they can use to compete with machines or computers. One of the skills is negotiation which involves mastering language, especially English as a means of international communication. However, learning English as a foreign language is not as easy as it seems. The students need to use a proper learning media which match their characteristics as digital native and motivate them in learning English such as multimedia. By using multimedia, the students will not only learn about language but also the skill about how to use the media or a computer to come up with industrial revolution 4.0. Thus, the researchers who are English lecturers aimed to encourage students in Universitas Teknokrat Indonesia (UTI) to use more web-based medium as a medium in learning English in a class, exclusively Powtoon. This research used a qualitative method since it disclosed how UTI students use Powtoon in a class and what their opinion toward Powtoon for learning English. During the research, the students used Powtoon in a class as a presentation medium for a half-semester because after mid-test they were divided into 13 groups to present the topics given by the lecturer. For each meeting, there were 2-3 groups presentation. At the end of the semester, the students were given questionnaire related to multimedia usage and responded that they felt motivated in learning English by using technology especially Powtoon. As a result, using a web-based medium in learning English can increase not only student’s ability to language but also technology.